TINDAK TUTUR DIREKTIF GURU DALAM PROSES PEMBELAJARAN BAHASA INDONESIA DI SMKS PENERBANGAN NUSANTARA KETAPING - Wahyuni, Neneng (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
This research is motivated by the problem of misunderstanding between students and teachers in the learning process. This misunderstanding occurs because students are not able to understand the intentions and goals of the teacher. The goals and objectives of the teacher cannot be well received by students because the form of speech acts that teachers use are not appropriate to the situation when they speak. The purpose of this study is to describe the politeness of language in the speech acts of the teacher directive in learning Indonesian at Nusantara Ketaping Flight SMKS, which is limited to the types of speech acts asking and begging. The results of the study showed that the forms of speech acts were instructed and begged that the teacher used in the learning process, both directly and indirectly. Keywords: speech acts, directive, teacher, learning